2008
DOI: 10.1186/1472-6823-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of sitagliptin in patients with type 2 diabetes: a pooled analysis

Abstract: Background: Sitagliptin, a highly selective dipeptidyl peptidase-4 inhibitor, is the first in a new class of oral antihyperglycemic agents (AHAs) for the treatment of patients with type 2 diabetes. Type 2 diabetes is a life-long disease requiring chronic treatment and management. Therefore, robust assessment of the long-term safety and tolerability of newer therapeutic agents is of importance. The purpose of this analysis was to assess the safety and tolerability of sitagliptin by pooling 12 large, double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 34 publications
6
85
1
2
Order By: Relevance
“…These results are consistent with those of a recent meta-analysis on patient-level data from trials with sitagliptin, which included only a fraction of the studies summarized in the present meta-analysis, and which showed a similar trend toward the increase of risk of nasopharyngitis with the DPP-4 inhibitor, although it failed to reach statistical significance [31]. It should be considered that DPP-4 is involved in the interaction between immune cells and that it could therefore modulate immune responses [32]; however, there is no evidence from mechanistic studies that inhibition of DPP-4 with currently available agents has an immunodepressant effect.…”
Section: Placebo-controlled Trials Active Comparatorssupporting
confidence: 81%
See 2 more Smart Citations
“…These results are consistent with those of a recent meta-analysis on patient-level data from trials with sitagliptin, which included only a fraction of the studies summarized in the present meta-analysis, and which showed a similar trend toward the increase of risk of nasopharyngitis with the DPP-4 inhibitor, although it failed to reach statistical significance [31]. It should be considered that DPP-4 is involved in the interaction between immune cells and that it could therefore modulate immune responses [32]; however, there is no evidence from mechanistic studies that inhibition of DPP-4 with currently available agents has an immunodepressant effect.…”
Section: Placebo-controlled Trials Active Comparatorssupporting
confidence: 81%
“…In fact, DPP-4 inhibitors do not induce any additional risk, in comparison with a placebo, either in monotherapy or in combination with sulphonylureas or insulin. This confirms the results of a recent meta-analysis performed on patientlevel data from randomized clinical trials with sitagliptin [31]. Interestingly, in the only trial performed in insulintreated patients, vildagliptin reduced the incidence of hypoglycemia in comparison with a placebo [20].…”
Section: Placebo-controlled Trials Active Comparatorssupporting
confidence: 78%
See 1 more Smart Citation
“…52 A meta-analysis has been published in regard to adverse events with sitagliptin in 12 large, doubleblind studies with durations from 18 weeks to 2 years. 70 The meta-analysis comprised a total of 3415 patients treated with sitagliptin (100 mg daily) and 2724 controls, who were treated either with other antihyperglycemic agents or placebo. The overall incidence of adverse events in these studies was 63% in patients given sitagliptin versus 63% in controls, ie, the same degree of total number of events.…”
Section: Dovepressmentioning
confidence: 99%
“…5 It should be remembered that acute pancreatitis and biliary disease is more common in type 2 diabetic patients compared with nondiabetic subjects. 6 There are no long-term data on cardiovascular outcomes such as MI and stroke for DPP-4 inhibitors, but…”
Section: Adverse Effectsmentioning
confidence: 99%